Review of Methods for Detection Helicobacter pylori in Kazakhstan - Lavrinenko Alyona; Seisenbekova Aizhan; Turemuratova Aidana; Shkreba Alexey; Yukhnevich Yekaterina (JGH Open)
ABSTRACT Helicobacter pylori (H. pylori) infection can cause a wide range of gastrointestinal disorders, including chronic nonatrophic gastritis, multifocal atrophic gastritis, peptic ulcer disease, gastric adenocarcinoma, and extra‐nodal B‐cell lymphoma. Although the prevalence of H. pylori infection has decreased among adults, it is still very common. Approximately 90% of gastric adenocarcinomas are associated with H. pylori infection. Despite the established link between H. pylori infection and noncardiac gastric cancer, and the increasing incidence of gastric cancer in Kazakhstan, there are limited data on the prevalence of H. pylori in the country. This may be due to the difficulty of detecting H. pylori and the unavailability of diagnostic methods. This review presents the current data of diagnostic tests for the detection of H. pylori in Kazakhstan with a focus on limitations and practical significance.